Diagnosis and Treatment of Adrenocortical Oncocytoma: Case Report of Five Cases and Review of the Literature - Dong, Dexin; Liu, Xiao; Ji, Zhigang; Li, Hanzhong (Frontiers in Oncology, 2019)
Objective To investigate the diagnosis and treatment of adrenocortical oncocytoma, and have a literature of review. Materials and methods The clinical data of 5 cases of adrenocortical oncocytoma treated in our hospital was retrospectively analyzed. The clinical manifestations, imaging examination, endocrine examination and pathological results were analyzed respectively. Results Oncocytic adrenocortical neoplasms are usually discovered incidentally without clinical manifestations. The oncocytic adrenocortical neoplasms lack specific imageological features, and imaging examination is mainly used for tumor localization and assisted diagnosis. There were no definite CT or MRI criteria available to help the differential diagnosis from benign to malignant tumors. The diagnosis of adrenocortical oncocytoma mainly depends on the pathological examination, and the therapy of oncocytic adrenocortical neoplasms mainly relies on surgery. Conclusions The diagnosis of adrenocortical oncocytoma mainly depends on the pathological examination, and surgical resection is the first choice.